Converses with the Grave: Three Modern Gaelic Laments - Chelsey MacPherson; Brian James MacLeod; Lodaidh MacFhionghain; Laurie Stanley-Blackwell (Genealogy, 2021)
Within Scottish deathways, the Gaelic lament has long served as a poignant and powerful outlet for loss. In this creative piece, three Canadian-born, Gaelic-speaking poets present their previously unpublished Gaelic laments along with English translations. This collaborative article is designed to demonstrate, in a creative rather than an academic format, that the venerable lament tradition continues to enjoy longevity and vitality in the present day as a literary expression of grief among Gaels. This article further demonstrates that modern Gaelic laments are not constrained by a strict fidelity to literary rules but strive instead to work creatively within tradition while reaching their audiences in a relevant and resonant way. For each poem, the author offers a personal contextualization for his/her lament, which serves to explain the source of inspiration and demonstrates how the work draws upon and reflects its literary roots. In recognition of the strong oral tradition present within Gaelic poetry, this article includes an audio recording of each of the three authors’ laments.